Will psilocybin lose its magic in the clinical setting? - Caroline Hayes; Mourad Wahba; Stuart Watson (SAGE Publishing, 2022)
Psilocybin as a novel treatment for depression is garnering a lot of attention from both the mainstream media and the academic community. Although phase 3 trials are only just beginning, we feel that it is important for clinicians to consider what psilocybin-assisted psychotherapy might look like in the clinical setting. In this narrative review article we have considered the difficulties that may arise as psilocybin emerges from the research setting, which may hamper its progress towards becoming a licenced medication. Psilocybin has its own unique challenges: the expectation patients come to dosing with having read overwhelmingly positive media; patient suggestibility under the influence of psilocybin and requirement for specialised therapists to name a few. We have also made some recommendations for measures that should be taken in both the phase 3 trials and with clinicians to try and minimise some of the issues raised. In doing so our hope is that psilocybin will continue towards becoming a licenced medication that suitable patients are able to access with relative ease. Practicing psychiatrists need to have an awareness of the potential pitfalls of psilocybin as they will be responsible for prescribing it in the future.